2019
DOI: 10.1002/cbic.201800736
|View full text |Cite
|
Sign up to set email alerts
|

A Promiscuous Cytochrome P450 Hydroxylates Aliphatic and Aromatic C−H Bonds of Aromatic 2,5‐Diketopiperazines

Abstract: Cytochrome P450 enzymes generally functionalize inert C−H bonds, and thus, they are important biocatalysts for chemical synthesis. However, enzymes that catalyze both aliphatic and aromatic hydroxylation in the same biotransformation process have rarely been reported. A recent biochemical study demonstrated the P450 TxtC for the biosynthesis of herbicidal thaxtomins as the first example of this unique type of enzyme. Herein, the detailed characterization of substrate requirements and biocatalytic applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 62 publications
0
14
0
2
Order By: Relevance
“…Coupled with TB14, the three-enzyme reaction synthesized 36 thaxtomin D analogues ( Jiang et al., 2018 ). Finally, we generated a self-sufficient TxtC variant TCB14 and used it to produce 58 hydroxylated thaxtomin analogues and 43 hydroxylated desnitro thaxtomin analogues ( Jiang et al., 2018 , 2019 ). The use of multiple native and engineered NRPS modules for the synthesis of NRP analogues from simple building blocks was further demonstrated in vitro in the synthesis of antibiotics tyrocidine A and 10 analogues ( Niquille et al., 2021 ) ( Figure 4 B).…”
Section: Biocatalytic Approaches For the Synthesis Of Nrpsmentioning
confidence: 99%
“…Coupled with TB14, the three-enzyme reaction synthesized 36 thaxtomin D analogues ( Jiang et al., 2018 ). Finally, we generated a self-sufficient TxtC variant TCB14 and used it to produce 58 hydroxylated thaxtomin analogues and 43 hydroxylated desnitro thaxtomin analogues ( Jiang et al., 2018 , 2019 ). The use of multiple native and engineered NRPS modules for the synthesis of NRP analogues from simple building blocks was further demonstrated in vitro in the synthesis of antibiotics tyrocidine A and 10 analogues ( Niquille et al., 2021 ) ( Figure 4 B).…”
Section: Biocatalytic Approaches For the Synthesis Of Nrpsmentioning
confidence: 99%
“…Das Wildtypenzym P450 TxtC ermçglicht aliphatische sowie aromatische C-H-Hydroxylierungeni nd er späten Funktionalisierung eines Diketopiperazins (18). [57,58] Zudem berichten aktuelle Beispiele über die Dihydroxylierung zweier aliphatischer oder aromatischer C-H-Bindungen innerhalb eines Vitamin-D2-Motivs bzw.A rens: [59,60] Wildtyp-CYP109E1 hydroxyliert Vitamin D2 hochgradig regio-und stereoselektiv in einer Zwei-Schritt-Dihydroxylierung (Abbildung 7). [59] Darüber hinaus wurden P450-Enzyme im Hinblick auf multiple Oxyfunktionalisierungen konstruiert.…”
Section: Hydroxylierungunclassified
“…1,2 Thxs are often pursued as herbicides for crop protection due to their virulence. 3,4 However, the synthetic routes to Thxs suffered from the lack of stereo-control and low overall yield. 5,6 Recently, it was reported that TxtC is able to effectively produce thaxtomin A, an herbicide approved by the U.S Environmental Protection Agency (EPA), 3,4,7 from thaxtomin D. TxtC is a member from cytochrome P450 family which consists of versatile monooxygenases to execute a broad array of biochemical transformations, such as, hydroxylation of alkane, oxidation of heteroatoms or aromatics, and dealkylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, the synthetic routes to Thxs suffered from the lack of stereo-control and low overall yield. 5,6 Recently, it was reported that TxtC is able to effectively produce thaxtomin A, an herbicide approved by the U.S Environmental Protection Agency (EPA), 3,4,7 from thaxtomin D. TxtC is a member from cytochrome P450 family which consists of versatile monooxygenases to execute a broad array of biochemical transformations, such as, hydroxylation of alkane, oxidation of heteroatoms or aromatics, and dealkylation reactions. [8][9][10][11][12] In these catalytic reactions, the active high-valent iron-oxo porphyrin πcation radical (Cpd I, as shown in Scheme 1A) species serves as the oxygen source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation